Environmental effectiveness of GAEC cross-compliance standard 1.1c ‘Maintenance of farm channel networks and field convexity’ and economic evaluation of the competitiveness gap for farmers - Bazzoffi, Paolo; Pellegrini, Sergio; Carnevale, Silvia; Borrelli, Lamberto; Speroni, Marisanna; Furlan, Lorenzo; Chiarini, Francesca; Colauzzi, Michele; Fracasso, Francesco; Fedrizzi, Marco; Guerrieri, Mirko; Pagano, Mauro; et al. (Italian Journal of Agronomy, 2016)
This paper shows the results of the monitoring carried out in three farms of the project MO.NA.CO. in order to verify the effectiveness of the cross-compliance standard 1.1c which obliges the farmer to the ‘Maintenance of farm channel networks and field convexity’ in order to ensure its efficiency and functionality in draining water. It was also examined the competitiveness gap induced to the agricultural enterprise by the application of the standard, that is to say the additional costs borne by the beneficiary of the single payment determined by cleaning farm collector channels. Effectiveness was determined by evaluating the degradation of soil structure at the end of winter, on flat fields sown in autumn with winter wheat, in the two cases: a) Factual (channels along the field edges not clogged and no waterlogging present on the cultivated soil) b) Counterfactual (channels clogged and waterlogging present on the cultivated soil). The monitoring confirmed a positive effect of the adoption of this standard on predisposing soil to the ideal conditions for the maintenance of the structure. Despite the statistical evidence found, it must be said that the change in the surface roughness factor was so small as not to take any practical significance in order to affirm that the functional maintenance of collectors channels have been effective in reducing erosion. Overall, the soils were unstructured and crusted at the end of the observation period. Indexes Icli, NTU, and DS show a structural fragility from medium to high for soils of the three monitoring farms. This explains the lack of appreciable differences in the soil roughness parameter, especially in relation to heavy rains and long waterlogging periods in the cropping years of monitoring. The competitiveness gap induced by the application of this standard, amounted to 19.89±€ 6.35 ha-1 year-1. Atmospheric emission of CO2, was equal to 14.53±6.62 kg ha-1 year-1. It is considered important to point out that at the present Annex II: ‘Rules of cross-compliance’ of Regulation (EU) No. 1306/2013 includes a BCAA not taking into account the environmental threats determined by waterlogging in cultivated land to soil, crops and to atmosphere, due to the possible production of greenhouse gases. As regards the infringement criteria to the standard it is suggested the introduction of the verification of the presence of convexity on cultivated fields in the plain.